Strategi Adaptasi Guru Dalam Meningkatkan Kompetensi Pasca Peraturan Baru Bagi Guru MGMP IPS Kabupaten Batang - Atika Wijaya; Tri Marhaeni Pudji Astuti; Elly Kismini; Wulan Dwi Aryani; Zaematul Mahbubah; Anisya Rahmadani; Elsha Pipit Nathalia (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The 2023 new regulations for ASN (public civil servants) have caused changes and anxiety for teachers. With this new regulation, all ASN will have functional positions which are expected to make regulations and promotion processes easier and simpler. ASN teachers will focus on organizational performance achievements, whereas previously, to apply for a promotion, civil servants focused on fulfilling credit or DUPAK numbers which were too administrative and troublesome. However, many teachers' career problems are now increasingly unclear due to the publication of this new policy. So, there is a need for activities to accompany teachers in strengthening their careers after the implementation of the new policy. The implementation method used in this community service program is socialization and mentoring. With this program, it is hoped that middle school social studies teachers throughout Batang Regency can understand the new regulations and plan their career paths appropriately.